Alcohol-related consequences and the intention to seek care in treatment naïve women and men with severe alcohol use disorder. (August 2022) - Conner, Kenneth R.; Abar, Beau; Aldalur, Aileen; Chiang, Andrew; Hutchison, Morica; Maisto, Stephen A.; Stecker, Tracy
Highlights: Examined alcohol-related consequences and intention to seek care in adults with severe alcohol use disorder. Interpersonal consequences were associated with intention to seek treatment in both women and women. Intrapersonal consequences (e.g., sadness) were more strongly associated with intention in women. Financial difficulties were related to increased intention in men only. Abstract: Introduction: Research on treatment utilization for alcohol use disorder (AUD) is based primarily on clinical samples and community samples of low AUD severity that may not need formal care. Using a community sample of adults with untreated but severe AUD symptoms, we tested the hypothesis that alcohol-related consequences, but not alcohol consumption levels, are associated with the intention to seek AUD treatment, examined associations of specific types of alcohol-related consequences with intention, and explored sex differences in these associations. Methods: The sample was recruited using social media ads for a randomized controlled trial to test a brief intervention to promote AUD treatment seeking. This report is based on analysis of baseline data collected prior to treatment intervention. Multiple linear regressions examined associations of measures of alcohol consumption, alcohol-related consequences broadly, and specific alcohol-related consequences with the intention to seek treatment. Moderating effects of sex on associations were explored. Results: Subjects (n = 349) averaged 41 years of age, 48% were female, 6% were Latinx, 80% were white, 15% were Black, and 92% met criteria for severe AUD. Alcohol consumption measures were not associated with intention to seek treatment whereas interpersonal- and intrapersonal- consequences were associated with intention. Sex served as a moderator, with intrapersonal consequences (e.g., sad mood) showing a stronger association with intention in women and social responsibility consequences (particularly financial) associated with intention in men. Conclusion: Select alcohol-related consequences may be keys to understanding increased intention to seek AUD treatment including intrapersonal consequences in women and financial consequences in men.